2012
DOI: 10.1007/978-3-642-31404-9_18
|View full text |Cite
|
Sign up to set email alerts
|

Vibrotactile Stimulation Can Affect Auditory Loudness: A Pilot Study

Abstract: Abstract. Very few cases have been reported where tactile stimulation affects auditory perception. In this pilot study, we asked volunteers to compare the loudness of combinations of vibrotactile and auditory stimuli. A 50-300 Hz band-limited pink noise signal was used as the stimulus in the two modalities, simultaneously heard through headphones and felt in the hands to be compared to when it was heard only. On average, the same auditory stimulus was judged to be about one dB louder when it was simultaneously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…In our previous paper, we reported that the subjective auditory intensity, which is one of the basic perceptual attributes, becomes louder by adding tactile vibration using the same source as the sound [10].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous paper, we reported that the subjective auditory intensity, which is one of the basic perceptual attributes, becomes louder by adding tactile vibration using the same source as the sound [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, this response pattern was not observed when the standard was auditory. Although, in our case both standard and comparisons are always auditory-haptic, a condition not considered in [13], it remains unclear to what extent these kinds of response order effects played a role.…”
Section: Effects Of Stimulus Presentation Ordermentioning
confidence: 87%
“…These kinds of biases are apparently complicated further by other factors such as sensory modality. For instance, Okazaki et al [13] tested a number of standard and comparison conditions. On half the conditions the standard was haptic and in the other the standard was auditory.…”
Section: Effects Of Stimulus Presentation Ordermentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the results presented here suggest that research on active touch in musical performance may prove precious to understand the role, mechanisms, and prospective applications of active touch perception also outside the musical context. An example application that seems at immediate reach of current tactile interfaces is to create illusory effects of loudness change by varying the intensity of vibratory feedback [39,42].…”
Section: Discussionmentioning
confidence: 99%